An exploration of teacher attrition and mobility in high poverty racially segregated schools. Issue 5 (2nd September 2016) - Djonko-Moore, Cara M.
Abstract : The purpose of this study was to examine the mobility (movement to a new school) and attrition (quitting teaching) patterns of teachers in high poverty, racially segregated (HPRS) schools in the US. Using 2007–9 survey data from the National Center for Education Statistics, a multi-level multinomial logistic regression was performed to examine the contribution of teacher characteristics, school setting characteristics, and school climate with a focus on interactions between school climate variables. The findings demonstrated that school climate variables predicted increased odds of mobility and that teacher characteristics, school setting, and teachers' perceptions of school climate predicted increased odds of teacher attrition. These findings suggest that teacher attrition and mobility from HPRS schools could be slowed by strategic placement of teachers based on their beliefs about students in poverty and students of color.